The Psychometric Properties of the ACIE Test for the Identification of High Intellectual Abilities - Andrade, Xavier Torres; Yépez, Alba Moreno; Núñez, Aracelly Naranjo; Remache, Gonzalo Bunci; Toro , Soraya Santacruz (Journal of Ecohumanism, 2024)
High intellectual abilities reflect outstanding qualitative and quantitative performance. It involves aptitudes, talents, and skills that surpass common standards. The main objective was the construction and validation of the High Intellectual Abilities Execution Test (ACIE). The methodological process involved administering the test structured with 117 items distributed across 5 dimensions. The pilot study was conducted with 164 students from fourth to seventh grade in four schools in the capital of Ecuador. Psychometric qualities such as reliability, validity, difficulty, discrimination power, and differential analysis were identified, providing the technical conditions for the application and detection of high abilities.